2019
DOI: 10.1063/1.5084759
|View full text |Cite
|
Sign up to set email alerts
|

Plasma passivation of near-interface oxide traps and voltage stability in SiC MOS capacitors

Abstract: Near-interface oxide traps severely affect the voltage stability of silicon carbide metal-oxide-semiconductor devices. In this work, electron cyclotron resonance microwave nitrogen plasma and electron cyclotron resonance microwave nitrogen-hydrogen-mixed plasma were used to passivate near-interface oxide traps in silicon carbide metal-oxide-semiconductor capacitors. An improved low-temperature midgap voltage drift method was proposed to evaluate the voltage stability of silicon carbide metal-oxide-semiconducto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…Δ N ot can be calculated by normalΔ N normalo normalt = normalΔ V normalm normalg , normalh normaly normals normalt normale normalr normale normals normali normals × C normalo normalx italicAq where C ox is the oxide capacitance, A is the electrode area, and q is the elementary charge. The blue dashed line in Figure b represents the Δ N ot of all samples under alternate bias stress at 100 K. The Δ N ot is decreased for the samples pretreated by NH plasma, and the Δ N ot of NH-8 min is the lowest (8.28 × 10 10 cm –2 , as shown in Table S3), which is lower than that of the samples prepared by NH and NO postoxidation annealing. , The results demonstrate that NH plasma pretreatment could effectively inhibit oxide traps generated by thermal oxidation by reducing defects on the SiC surface.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations
“…Δ N ot can be calculated by normalΔ N normalo normalt = normalΔ V normalm normalg , normalh normaly normals normalt normale normalr normale normals normali normals × C normalo normalx italicAq where C ox is the oxide capacitance, A is the electrode area, and q is the elementary charge. The blue dashed line in Figure b represents the Δ N ot of all samples under alternate bias stress at 100 K. The Δ N ot is decreased for the samples pretreated by NH plasma, and the Δ N ot of NH-8 min is the lowest (8.28 × 10 10 cm –2 , as shown in Table S3), which is lower than that of the samples prepared by NH and NO postoxidation annealing. , The results demonstrate that NH plasma pretreatment could effectively inhibit oxide traps generated by thermal oxidation by reducing defects on the SiC surface.…”
Section: Resultsmentioning
confidence: 80%
“…In addition, the improvement of BTI of the SiC MOS device is ascribed to the passivation of C-related defects by N atoms and the reduction of interfacial defects. SiO x C y and C–C generally exist as near-interface oxide traps, and the corresponding defective energy levels are located near the CBM in the SiC band gap, which seriously affects BTI . NH plasma pretreatment suppressed the generation of these interface electroactive traps by eliminating surface contaminants and passivating surface defects; the introduced N atoms at the interface could also effectively passivate these defects, converting the defect energy level from near the CBM to the lower half of the SiC band gap or outside of the band gap, thus limiting the capture of defect carriers and further improving the BTI of the device …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[9,34] Second, a low temperature can reduce the de-trapping rate of trapped carriers. [9,35] Therefore, the electrical signals of many traps can be tested by C-V curves. We observed that ∆V fb decreases with the increase in O 3 oxidation temperature, indicating that V fb BTI can be effectively improved by O 3 oxidation at high temperatures.…”
Section: The V Fb Stability Under Btsmentioning
confidence: 99%